2020
DOI: 10.32794/mr11250075
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of melatonin’s protection against high-LET radiation: implications for space travel

Abstract: During a deep space mission, the central nervous system (CNS) and other organs are exposed to galactic cosmic rays and solar particle events. Health risks associated with various organs and systems are important issues in a long-term spaceflight. Potential CNS damage during a space mission could alter cognitive functions which might impact performance and individual’s health. The neuronal injury originating from exposure to 56Fe particle irradiation involves the elevated oxidative stress which can be inhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Melatonin treatment also significantly prevented carbon ion irradiation induced mitochondrial dysfunction and apoptosis in mouse brain, and alleviated the carbon induced increase in the percentage of apoptotic cells and elevated oxidative stress in mouse testis. 34 Melatonin has also shown radioprotective effects in erythrocytes, ovary, thyroid and liver of irradiated rodents, as well as in human lymphocites. 30 In humans, a double-blind placebo-controlled study in patients with rectum cancer undergoing radiotherapy examined the radioprotective effects of melatonin (20 mg/day, 5 days a week, during 28 days) on blood cell counts.…”
Section: Radiation Exposurementioning
confidence: 99%
“…Melatonin treatment also significantly prevented carbon ion irradiation induced mitochondrial dysfunction and apoptosis in mouse brain, and alleviated the carbon induced increase in the percentage of apoptotic cells and elevated oxidative stress in mouse testis. 34 Melatonin has also shown radioprotective effects in erythrocytes, ovary, thyroid and liver of irradiated rodents, as well as in human lymphocites. 30 In humans, a double-blind placebo-controlled study in patients with rectum cancer undergoing radiotherapy examined the radioprotective effects of melatonin (20 mg/day, 5 days a week, during 28 days) on blood cell counts.…”
Section: Radiation Exposurementioning
confidence: 99%
“…FYN upregulation reduces ROS, diminishing the indirect damage of ionising radiation [ 92 ]. Furthermore, Liu and Reiter [ 93 ] found that exposure of neurons to iron ion particle radiation leads to increased ROS levels that can be counteracted by melatonin treatment. This treatment also increased the number of immature neurons and proliferating cells in mice, which is a sign of an enhanced regenerative capacity of the neurons [ 93 ].…”
Section: General Effects Of Radiation On Dna/cancer Cellsmentioning
confidence: 99%
“…Ionising radiation produces ROS in cells and the extracellular environment, and several authors have discovered an upregulation of ROS scavengers and an increase in intercellular signalling of inflammation following irradiation. However, these changes can be counteracted by administering redox scavengers or antioxidants, effectively reducing the amount of ROS in the extracellular environment and possibly reducing intercellular inflammatory signalling, hinting at the possibility of using pharmaceutical protection against radiation-induced damage [ 89 , 90 , 91 , 92 , 93 ].…”
Section: General Effects Of Radiation On Dna/cancer Cellsmentioning
confidence: 99%